Characterization and adsorption capacity of Amine-SiO2 material for nitrate and phosphate removal - Toan, Phan Phuoc; Thanh, Nguyen Trung; Huy, Nguyen Nhat; Hang, Le Ngoc; Thich, Le Tri (Vietnam Journal of Science and Technology, 2019)
Amine-SiO2 material was synthesized and applied as a novel adsorbent for nitrate and phosphate removal from aqueous solution. The characterization of Amine-SiO2 were done by using TGA, FTIR, BET, and SEM analyses. Results showed that Amine-SiO2 had higher nitrate and phosphate adsorption capacity of 1.14 and 4.16 times, respectively, than commercial anion exchange resin (Akualite A420). In addition, Amine-SiO2 also had good durability with stable performance after at least 10 regeneration times, indicating that this material is very promising for commercialization in the future as an adsorbent for water treatment.